The Multiple Roles of B Cells in the Pathogenesis of Sjögren’s Syndrome - Du, Wenhan; Han, Man; Zhu, Xiaoxia; Xiao, Fan; Huang, Enyu; Che, Nan; Tang, Xiaopo; Zou, Hejian; Jiang, Quan; Lu, Liwei (Frontiers in Immunology, 2021)
Primary Sjögren’s syndrome (pSS) is a chronic autoimmune disease characterized by lymphocytic infiltration and tissue destruction of exocrine glands such as salivary glands. Although the formation of ectopic lymphoid tissue in exocrine glands and overproduction of autoantibodies by autoreactive B cells highlight the critical involvement of B cells in disease development, the precise roles of various B cell subsets in pSS pathogenesis remain partially understood. Current studies have identified several novel B cell subsets with multiple functions in pSS, among which autoreactive age-associated B cells, and plasma cells with augmented autoantibody production contribute to the disease progression. In addition, tissue-resident Fc Receptor-Like 4 (FcRL4)+ B cell subset with enhanced pro-inflammatory cytokine production serves as a key driver in pSS patients with mucosa-associated lymphoid tissue (MALT)-lymphomas. Recently, regulatory B (Breg) cells with impaired immunosuppressive functions are found negatively correlated with T follicular helper (Tfh) cells in pSS patients. Further studies have revealed a pivotal role of Breg cells in constraining Tfh response in autoimmune pathogenesis. This review provides an overview of recent advances in the identification of pathogenic B cell subsets and Breg cells, as well as new development of B-cell targeted therapies in pSS patients.